The supply chain of Javan spitting cobra (Naja sputatrix) utilization in cobra satay businesses in Jakarta, Indonesia - SILVA EKAPUTRA UTAMA; YANTO SANTOSA; BURHANUDDIN MASYUD (Society for Indonesian Biodiversity, 2024)
Abstract. Utama SE, Santosa Y, Masyud B. 2024. The supply chain of Javan spitting cobra (Naja sputatrix) utilization in cobra satay businesses in Jakarta, Indonesia. Biodiversitas 25: 2086-2092. One frequently utilized reptile is the Javan spitting cobra (Naja sputatrix). Apart from Indonesia, countries that utilize cobras are China and India. One form of actual utilization for the community's economy from cobra utilization is the cobra satay business. The high economic potential threatens the cobra population in the wild. Moreover, trade in the supply chain can have a negative impact ecologically and economically, so it is necessary to approach the supply chain of the cobra business to understand the cobra supply chain, considering the roles of participants, distribution processes, the number and specifications of cobras utilized, the source of cobras, and the incurred losses within the supply chain. This research was conducted using the snowball sampling method, with in-depth interviews. Interviews with vendor were conducted at their shops in Jakarta, and interviews with agent and collector were conducted at their homes in Karawang. It enabled the identification of the supply chain of the cobra satay business consisting of vendor in Jakarta and collectors, agents, and hunters in Karawang. The data collected were the number, specifications, and prices of each supply chain link, as well as the form of cobra utilization from traders. An estimated ±1,560 cobras are used in the cobra satay business annually, with a minimum total length of 70 cm for the cobras. The results showed that the percentage of dead cobras in the supply chain was 5%-35%, which resulted in a reduction in income of Rp25,000 - Rp125,000 for agents, Rp40,000 - Rp240,000 for collector, and Rp200,000 - Rp2,000,000 for vendor.